Characterization of Self-Microemulsifying Dosage Form: Special Emphasis on Zeta Potential Measurement: Characterization of Self-Microemulsifying Dosage Form: Special Emphasis on Zeta Potential Measurement - Kulkarni, Nilesh S. (International Journal of Pharmaceutical & Biological Archive, 2019)
The emulsion is a disperse system which is thermodynamically unstable. To improve the stability of the disperse system microemulsion or nanoemulsion was prepared to improve thermodynamic stability. Zeta potential is a physical property which is exhibited by any particle in suspension/emulsion, i.e., in colloidal dispersion. It can be used to optimize the formulations of suspensions and emulsions. Zeta potential is the measure of overall charges acquired by particles in a particular medium and is considered as one of the benchmarks of stability of the colloidal system. As a rule of thumb, suspensions/dispersed system with zeta potential above 30 mV (absolute value) are physically stable. Suspensions with a potential above 60 mV show excellent stability. Suspensions below 20 mV are of limited stability; below 5 mV they undergo pronounced aggregation if the system is stabilized by the electrostatic mechanism. If the values are low for visually stable emulsions, it could be attributed to steric repulsion between approaching molecules, i.e., system is sterically stabilized. Such sterically stabilized colloidal systems though they have low zeta potential values are found to be stable during storage. Tween is well accepted steric stabilizer for colloidal systems. Stability of such a visually stable emulsion or microemulsions should be carried out under accelerated or long-term stability conditions to confirm the globule size and zeta potential on aging.